Analysis of Performance Measurement with the Balanced Score Card Approach at the Regional Water Company (PDAM) Tirta Dharma Bengkulu City - Echa Gunawan; Oni Yulianti; Wagini Wagini (Penerbit Jurnal Indonesia, 2021)
This study aims to conduct and see the overall organizational picture of the Bengkulu City Water Supply Company (PDAM) performance appraisal using the Balanced Scorecard approach. seen from four perspectives, namely: financial perspective, customer perspective, internal business perspective, and learning and growth perspective. From the results of research on the Performance Measurement of Regional Drinking Water Companies (PDAMs) Bengkulu City using the Balanced Scorecard approach from a financial perspective through current ratios, profit margins, operation ratios, return on investment shows that the company's financial performance is in good condition. For performance measurement based on customer perspective from customer acquistion, customer retention, customer satisfaction, customer satisfaction can be said to be good. Furthermore, the relationship / coleration of performance based on the perspective of internal business processes on the variables of motivation, alignment power, has a level of influence of 50.9% with a significance level of <5% or 0%, but for trainings it has a significance level of below 5% or equal to 0%. Whereas for performance based on the perspective of learning and growth on employee satisfaction, employee retention, productivity makes a positive contribution to the improvement of the company's economy.